Mental Health Impacts of the COVID-19 Pandemic on Australian Children and Adolescents with a Medical Condition: Longitudinal Findings - Louise M. Crowe; Cathriona Clarke; Dan Geraghty; Ben Collins; Stephen Hearps; Remy Pugh; Nicola Kilpatrick; Emma Branson; Jonathan M. Payne; Kristina Haebich; Natalie McCloughan; Christopher Kintakas; et al. (COVID)
In Melbourne, Australia, strict ‘lockdowns’ were implemented in 2020 to suppress COVID-19, significantly disrupting daily life. Young people (<18 years) with medical conditions have an elevated risk of mental health problems and may have been disproportionately affected by the distress associated with the COVID-19 restrictions. To investigate this, we conducted a single-site, longitudinal cohort study involving the parents of 135 children and adolescents with medical conditions. Using an adapted version of the CoRonavIruS Health Impact Survey (CRISIS), parents rated their child’s mental health, activities and healthcare experiences pre-COVID-19 (retrospectively), during lockdown and 6 months post-lockdown. General linear mixed models revealed that mental health symptoms, including anxiety, fatigue, distractibility, sadness, irritability, loneliness and worry, were higher during lockdown compared to pre-COVID-19. Notably, anxiety, sadness and loneliness remained elevated 6 months post-lockdown. Covariates such as older child age, increased parent stress and child screen time contributed to greater mental health difficulties. While most mental health symptoms resolved post-lockdown, the persistence of anxiety, sadness and loneliness highlights the need for ongoing clinical monitoring for young people with medical conditions during periods of community stress and restrictions.